Configuration of framework for utilising sharp waste bins in highway R&R / Mohamad Amir Razi Abdullah, Haszlin Shaharudin and Mohammad Azroll Ahmad - Abdullah, Mohamad Amir Razi; Shaharudin, Haszlin; Ahmad, Mohammad Azroll (Universiti Teknologi MARA, 2020)
It is important to acknowledge a systemized chain of networking elements that associate with other elements that will need to make sense of a path on structural integrity about a concept that it can progress towards visualizing a compelling result. A corresponding remark that was made by Stichler and Hamilton (2008) that they describe in their statements was delivered to predict or explain the connection among concepts, variables as well as notions of interest, as these notions are sound. The intention is to connect and compost a concept behind a certain inexplicit idea of clearing confusion and how it will work when tested, whether in theory or practice. It is the theory that a “plausible or scientifically acceptable general principle or body of principles offered to explain phenomena” (Merriam-Webster Online, 2020). This paper looks into the matter of the ways the Sharp Waste Bins can be adopted and put into a systematically appropriate purpose for society. In this case, in some way of rational sense, having to analyse the use of Sharp Waste Bins in Highway Rest & Recreational can be explained on how functional and ethical for the product to be mounted in public places, by exercising some thoughts on the plan of this idea through the use of the framework model